(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
The enforced disappearance in Argentina produced multiple forms of subjective affectation and rupture of social ties. Categories such as “relatives of the disappeared” or “survivors” –among others– delimit specific modalities in which State violence marked life trajectories. Areas of experience of “child victims” have been partially incorporated into the narratives of memory from a filiation-based matrix of meaning, while other children’s experiences remain occluded. In this article we address the activity “The Five O’Clock Visit” at the Museum Site of Memory ESMA, with the aim of reflecting on the ways in which these children’s experiences are thematised and the senses constructed by and around them.